2022
DOI: 10.2174/1871527320666210825112240
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biofactors in Diabetic Microvascular Complications

Abstract: : Microvascular complications are responsible for a major proportion of the burden associated with diabetes contributing to substantial morbidity, mortality, and healthcare costs in people with diabetes. Retinopathy, nephropathy, and neuropathy constitute the leading causes of blindness, end-stage renal disease, and lower-extremity amputations, respectively. Since the efficacy of causal therapies of diabetic microvascular complications is limited, especially in type 2 diabetes, there is an unmet need for adjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 272 publications
0
15
0
3
Order By: Relevance
“…144,145 Benfotiamine, a fat-soluble derivative of thiamine, acts by inhibiting the formation of advanced glycation end products, 146 thereby improving neuropathic symptoms in patients with DPN. 147,151 These nutraceuticals are well tolerated, with adverse event profiles similar to those with placebo.…”
Section: Disease Modificationmentioning
confidence: 99%
“…144,145 Benfotiamine, a fat-soluble derivative of thiamine, acts by inhibiting the formation of advanced glycation end products, 146 thereby improving neuropathic symptoms in patients with DPN. 147,151 These nutraceuticals are well tolerated, with adverse event profiles similar to those with placebo.…”
Section: Disease Modificationmentioning
confidence: 99%
“…ALA is a naturally occurring antioxidant and it is considered the most promising nutraceutical [6]. In clinical trials, 600 mg ALA acid has been shown to improve neuropathic deficits [10].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Increased exercise and a healthy diet, according to lifestyle interventions, may delay or even facilitate nerve fibre regeneration [5]. Surprisingly, there is some promising evidence on the role of vitamins and supplements in improving therapy [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, microalbumin urine is not a sensitive and specific predictor for prevalence and progression of DKD, as the sensitivity and specificity of microalbuminuria for early detection of disease are limited by a number of factors: high day-to-day variability of urine albumin excretion; the phenomenon of non-albuminuric diabetic nephropathy; and presence of advanced renal pathological changes by the time microalbuminuria is clinically detectable [9]. Although some studies have revealed that many biological markers or biomarkers can reflect the presence of microvascular damage in type 2 diabetes (T2D) patients [10,11], and are associated with development of T2D [12,13], their predictive power for DKD and its progression is still limited.…”
Section: Introductionmentioning
confidence: 99%